The Deubiquitinase USP13 Maintains Cancer Cell Stemness by Promoting FASN Stability in Small Cell Lung Cancer - Wang, Juhong; Lin, Weihao; Li, Renda; Cheng, Hong; Sun, Sijin; Shao, Fei; Yang, Yannan; Zhang, Lin; Feng, Xiaoli; Gao, Shugeng; Gao, Yibo; He, Jie (Frontiers in Oncology, 2022)
USP13 is significantly amplified in over 20% of lung cancer patients and critical for tumor progression. However, the functional role of USP13 in small cell lung cancer (SCLC) remains largely unclear. In this study, we found that the deubiquitinase USP13 is highly expressed in SCLC tumor samples and positively associated with poor prognosis in multiple cohorts. In vitro and in vivo depletion of USP13 inhibited SCLC cancer stem cells (CSCs) properties and tumorigenesis, and this inhibitory effect was rescued by reconstituted expression of wide type (WT) USP13 but not the enzyme-inactive USP13 mutant. Mechanistically, USP13 interacts with fatty acid synthase (FASN) and enhances FASN protein stability. FASN downregulation suppresses USP13-enhanced cell renewal regulator expression, sphere formation ability, and de novo fatty acids biogenesis. Accordingly, we found FASN expression is upregulated in surgical resected SCLC specimens, positively correlated with USP13, and associated with poor prognosis of SCLC patients. More importantly, the small molecule inhibitor of FASN, TVB-2640, significantly inhibits lipogenic phenotype and attenuates self-renewal ability, chemotherapy resistance and USP13-mediated tumorigenesis in SCLC. Thus, our study highlights a critical role of the USP13-FASN-lipogenesis axis in SCLC cancer stemness maintenance and tumor growth, and reveals a potential combination therapy for SCLC patients.